A dataset of drip patterns for teaching and research purposes in forensic bloodstain pattern analysisBorealis - Shaijieni Kannan; Stanard M. Pachong; Peter R. Lewis; Theresa Stotesbury (Data in Brief)
We present a dataset of 635 drip patterns using whole blood generated in indoor and outdoor conditions. Whole bovine blood with ACD-A anticoagulant was used to create the patterns. The patterns have varied numbers of drops and dripping heights across four substrates: paper, grass, ceramic tile, and snow. Blood fluid properties such as surface tension, viscosity, relative density, and packed cell volume were measured on the same day of blood collection. Temperature and relative humidity were recorded at the time of each experiment day. The key features were the number of drops, the type of substrate, and the impact height/velocity. This novel data set is suitable for research and training in the forensic discipline of bloodstain pattern analysis and enables method development and validation.